Wavefront-guided pupilloplasty in patients following penetrating keratoplasty: Optimizing results - Vijay K Sharma; GN Divyashree; Preeti; Vikas Ambiya; Ashok Kumar; Srishti Khullar; Vipin Rana (Indian Journal of Ophthalmology)
Purpose: To describe the role of wavefront-guided pupilloplasty in improving visual quality and wavefront parameters in post-keratoplasty patients with pathologically irregular, mydriatic pupils. Methods: A total of 13 eyes of post-penetrating keratoplasty patients with pathologically irregular mydriatic pupil were included in this prospective interventional study. Preoperative wavefront analysis was done with the actual pupil size, and predicted wavefront values were analyzed by setting the postoperative pupil size to 2 mm. Patients showing significant improvement between preoperative and predicted postoperative wavefront values underwent single-pass four-throw pupilloplasty, and all wavefront parameters were again evaluated after 1 week. Preoperative and postoperative best corrected visual acuity (BCVA), pupil size, and wavefront parameters were analyzed. Results: Mean BCVA improved from a preoperative value of 1.03 ± 0.32 log of minimum angle of resolution (logMAR) units to 0.24 ± 0.09 logMAR units. Mean preoperative pupil size was 6.077 ± 0.787 mm, whereas the achieved postoperative pupil size after pupilloplasty was 2.538 ± 0.139 mm. Mean astigmatism root mean square (RMS) value improved from 4.169 ± 3.876 to 0.875 ± 0.926 µm (P < 0.05), and mean coma value changed from 1.525 ± 1.962 to 0.128 ± 0.152 µm (P < 0.05). Mean point spread function Stehl ratio value improved from 0.056 ± 0.032 to 0.223 ± 0.102. Mean RMS (optical path difference) value changed from 6.248 ± 4.721 to 0.943 ± 0.947 µm (P < 0.001), Mean RMS (high orders) value changed from 3.788 ± 3.537 to 0.328 ± 0.256 µm (P value 0.003), and the mean spherical aberration value changed from 0.646 ± 0.873 to 0.223 ± 0.102 µm (P value 0.024). All postoperative wavefront parameters showed statistically significant improvement from the preoperative parameters. Conclusion: Wavefront-guided pupilloplasty can predict and improve wavefront parameters and visual quality in post-keratoplasty patients with pathologically irregular mydriatic pupils.